Challenges and opportunities in establishing an Health Examination Survey (Epidemiology, Biostatistics, and Public Health, 2022)
In Italy, the last 30 years witnessed the implementation of cross-sectional surveys providing baseline data on numerous risk factors collected from random samples of the adult general population.In order to support those groups who would like to implement an health examination survey (HES), according to the experience of  the CUORE Project surveys, the objective of this paper is to describe some information related to the organization of a survey (examination sites and sampling, selection of analytic laboratory, coordination and personnel involved, sample selection, recruitment and appointment scheduling, informative notice and informed consent, participation rate, non-participation bias, quality assurance, survey data, long term storage of the samples, internal quality control, external quality assessment, feedback to participants, error checking, correction and documentation of the data, transfer and storage of the data, statistical analyses and interpretation of results, dissemination of results), usually shortly described  in scientific papers but relevant when an HES is planned.